2021
DOI: 10.21037/tlcr-20-458
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for thymic epithelial tumours: a review

Abstract: Thymic epithelial tumours (TETs) represent a rare disease, yet they are the most common tumours of the anterior mediastinum. Due to the rare occurrence of TETs, evidence on optimal treatment is limited. Surgery is the treatment of choice in the management of TETs, while the role of postoperative radiotherapy (PORT) remains unresolved. PORT remains debated for thymomas, especially in completely resected stage II tumours, for which PORT may be more likely to benefit in the presence of aggressive histology (WHO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…, putting stages III and IV into one group ( 29 31 ). The role of postoperative radiotherapy is controversial in patients with advanced thymic tumors, but some reports have recommended it ( 32 34 ). Combined with the current research, considering that advanced thymic tumors cannot be completely resected, postoperative radiotherapy will benefit them.…”
Section: Discussionmentioning
confidence: 99%
“…, putting stages III and IV into one group ( 29 31 ). The role of postoperative radiotherapy is controversial in patients with advanced thymic tumors, but some reports have recommended it ( 32 34 ). Combined with the current research, considering that advanced thymic tumors cannot be completely resected, postoperative radiotherapy will benefit them.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, it is offered to patients who are deemed unresectable or borderline resectable upfront, to make the lesion resectable afterwards. Postoperatively, radiotherapy is given in patients who have undergone R1, R2 resection or in patients with complete resection of the tumour but who had an advanced stage (IIB-IV) at presentation [ 15 ]. In our study a total of 57 patients received RT, 44 in the adjuvant setting and 13 patients with the intent being radical (7 upfront and 6 after neoadjuvant chemotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is widely used to treat type B3 thymomas, but mostly for postoperative adjuvant treatment ( 4 , 5 ). We accidentally found that an aggressive type B3 thymoma lesion shrank significantly after radiotherapy, making radical treatment via single-incision thoracoscopy smoothly.…”
Section: Commentmentioning
confidence: 99%